Direct Access to β‐Fluorinated Aldehydes by Nitrite‐Modified Wacker Oxidation. Issue 29 (25th May 2016) - Chu, Crystal K.; Ziegler, Daniel T.; Carr, Brian; Wickens, Zachary K.; Grubbs, Robert H.
Abstract: An aldehyde‐selective Wacker‐type oxidation of allylic fluorides proceeds with a nitrite catalyst. The method represents a direct route to prepare β‐fluorinated aldehydes. Allylic fluorides bearing a variety of functional groups are transformed in high yield and very high regioselectivity. Additionally, the unpurified aldehyde products serve as versatile intermediates, thus enabling access to a diverse array of fluorinated building blocks. Preliminary mechanistic investigations suggest that inductive effects have a strong influence on the rate and regioselectivity of the oxidation. Abstract : Out of Wack(er) : The aldehyde‐selective Wacker‐type oxidation of allylic fluorides was accomplished using catalytic nitrite, thus providing a direct route to β‐fluorinated aldehydes. Allylic fluorides bearing a variety of functional groups are transformed in high yield and regioselectivity. Preliminary mechanistic investigations suggest that inductive effects have a strong influence on the rate and regioselectivity of the oxidation.